Preparing national regulations for water resources management : principles and practice / Stefano Burchi, Ariella D'Andrea for the Development Law Service, FAO Legal Office. - Burchi, Stefano. (FAO legislative study, 2003)
"The present manual is an update of Legislative Study No. 52 (1994). Like its predecessor, it provides conceptual material for use in the preparation of national regulations for the management, development, use and protection of freshwater resources. The conceptual material is arranged according to the principal functions of water resources management, and it is complemented and illustrated by examples of original water management regulations. These have been drawn from a wide variety of mostly English-speaking countries. The manual is intended for the inspiration and reference of a multidisciplinary water-sector audience and, in particular, all those in government who participate in the preparation of regulations for the implementation of policies and principles enshrined in acts of legislature"--Back cover.